Um modelo em simulink para sintonia automática de controladores PID usando redes neuronais - Lima, João (2013)
The PID controllers are widely used in industry. Whether because the plant is time-varying, or because of components ageing, these controllers need to be regularly retuned. During the last years, several methods have been proposed for PID autotuning.